Financial Performance Assessment Analysis in PT Magnum Attack Malang - Warsono; Anggi Yusniar; Chalimatuz Sa'diyah (Universitas Muhammadiyah Malang, 2022)
This study aims to determine the financial performance of PT Magnum Attack Malang which was studied using the Economic Value Added (EVA) method from 2017 to 2019. The type of research used is quantitative. Data collection was carried out using a documentation technique, namely the financial statements of PT Magnum Attack Malang for the period 2017 to 2019. The results of this study indicate that the Economic Value Added (EVA) value at PT Magnum Attack Malang in 2017 was 482,698,019, in 2018 it was 519,321. 979, and 2019 of 1,192,321,979 resulted in an EVA value > 0 meaning the company created economic added value. The conclusion of the financial performance at PT Magnum Attack Malang from 2017 to 2019 was analyzed using the Economic Value Added (EVA) method in a healthy condition.